Targeting PRAME directly or via EZH2 inhibition overcomes retinoid resistance and represents a novel therapy for keratinocyte carcinoma - Brandon Ramchatesingh; Amelia Martinez Villarreal; Philippe Lefrançois; Jennifer Gantchev; Sriraam Sivachandran; Samy Abou Setah; Ivan V. Litvinov (Molecular Oncology)
Retinoids have demonstrated efficacy as preventative/treatment agents for keratinocyte carcinomas (KCs): basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (SCC). However, retinoid resistance mechanisms limit the efficacy of these compounds. A subset of KCs expresses Preferentially Expressed Antigen in Melanoma (PRAME): a retinoid signaling corepressor. PRAME is proposed to repress retinoid signaling by guiding enhancer of zeste homolog 2 (EZH2) to retinoic acid response elements (RARE) in promoters. We investigated the effects of PRAME on KC pathogenesis and retinoid response. High‐PRAME expression in tumors was negatively correlated with epidermal differentiation gene signatures. PRAME overexpression downregulated epidermal differentiation gene signatures and impaired differentiation in 3D culture. PRAME overexpression attenuated retinoid‐induced RARE activation, growth suppression, and differentiation responses. Conversely, low‐PRAME tumors and PRAME‐depleted KC cells demonstrated enriched epidermal differentiation gene signatures. PRAME downregulation restored retinoid‐induced RARE activation, growth suppression, keratinization in SCC, and cell death signaling in BCC. Furthermore, combined retinoid and EZH2 inhibitor treatment augmented RARE activation and suppressed PRAME‐expressing KC cell growth. Hence, PRAME confers retinoid resistance in KC, which may be overcome by EZH2 inhibition.